Synthesis of Cyclic (Ethylene Furanoate) Oligomers via Cyclodepolymerization. Issue 4 (17th May 2018) - Fleckenstein, Peter; Rosenboom, Jan‐Georg; Storti, Giuseppe; Morbidelli, Massimo
Abstract: High molecular weight polyethylene furanoate (PEF) is a potential replacement for polyethylene terephthalate. Ring‐opening‐polymerization of PEF can represent a viable alternative to the classical polycondensation process, provided that a synthesis route is available to supply high purity cycles in high yields. In this work, cyclic oligomers of PEF are produced by cyclodepolymerization (CDP). Reactions are performed in different high boiling solvents and 2‐methylnaphthalene (2‐MN) is chosen as a favorable reaction solvent for a detailed analysis of the reaction equilibrium behavior of cyclic and linear PEF. Such equilibrium can be described by the well‐known model of Jacobson and Stockmayer. The corresponding equilibrium constants are first determined by fitting a set of equilibrium data. Based on this description of the reaction, a kinetic model is then developed and validated by comparison with experimental data. Finally, selective precipitation is shortly explored as a practical purification method which, together with CDP, can enable a large scale process for the production of high purity cyclic PEF oligomers for ring‐opening‐polymerization. Abstract : A thorough investigation of cyclodepolymerization (CDP) for the production of cyclic oligomers of polyethylene furanoate (PEF) is performed. This is the first step in the production of the renewable resource based polymer PEF by ring‐opening polymerization (ROP). Several solvents are examined to evaluate their performance in CDP reactions. Finally a kinetic model is developed and validated, able to describe the equilibration of cyclic and linear oligomers at different concentrations.